1993
DOI: 10.1037/h0095600
|View full text |Cite
|
Sign up to set email alerts
|

Creating positive vocational outcomes for people with severe mental illness.

Abstract: This article is meant to serve as a practical guide to the various vocational alternatives currently in use in the psychiatric rehabilitation field. It presents both benefits and drawbacks to the service recipient, o f each o f the models described. A perspective is offered on some parallel developments in employment services for people with mental illness and those with developmental disabilities. Finally, consideration is given to using links with the public Vocational Rehabilitation system as part o f the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 15 publications
0
28
1
Order By: Relevance
“…Although Marrone (1993) noted that certain Clubhouses did not include transitional employment in their services; a study by Macias, Jackson, Schroeder, and Wang (1999) found that 82% of Clubhouses (N ¼ 173) included transitional employment programs. In general, Clubhouses use participation in activities (work-ordered day) to develop the clients' motivation to enter transitional employment (Blankertz & Robinson, 1996;Macias, Kinney, & Rodican, 1995).…”
Section: Transitional Programsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although Marrone (1993) noted that certain Clubhouses did not include transitional employment in their services; a study by Macias, Jackson, Schroeder, and Wang (1999) found that 82% of Clubhouses (N ¼ 173) included transitional employment programs. In general, Clubhouses use participation in activities (work-ordered day) to develop the clients' motivation to enter transitional employment (Blankertz & Robinson, 1996;Macias, Kinney, & Rodican, 1995).…”
Section: Transitional Programsmentioning
confidence: 96%
“…In certain settings, prevocational activities within sheltered workshops are mandatory before accessing transitional employment, whereas others promote accelerated placement in transitional settings (Bond & Dincin, 1986). According to Marrone (1993), there are some advantages to transitional employment, such as the fact that the contracts are time-limited and give employees the possibility of attaining significant work experience in various settings. The disadvantages are that the jobs offered are often unskilled and time-limited; regardless of their job performance and satisfaction, the worker will eventually need to vacate the position.…”
Section: Transitional Programsmentioning
confidence: 98%
See 2 more Smart Citations
“…Rapid job entry, transitional work experience (time-limited, entry-level jobs for purposes of work experience rather than career development), intensive case management (relying on direct support and involvement rather than brokering services), and wraparound services (marshalling multiple systems to focus comprehensively on the individual's needs rather than assisting the person to access these services individually) have also proven effective (Becker et al, 2001;Drake et al, 2001;Marrone, 1993;MDRC, 2001;Phillips et al, 2001, Shaheen, Williams, & Dennis, 2003.…”
Section: Introductionmentioning
confidence: 99%